2021
DOI: 10.3390/jcm10194350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dosing Interval on Compliance of Osteoporosis Patients on Bisphosphonate Therapy: Observational Study Using Nationwide Insurance Claims Data

Abstract: Only a few studies are available on the effect of the dosing interval of bisphosphonate on drug compliance. We analyzed the data of patients who were newly prescribed bisphosphonate using a national insurance claims database. Drug compliance was assessed by calculating medication possession ratio (MPR) over a minimum of a 1-year follow-up. This analysis included 281,996 new bisphosphonate users with a mean age of 68.9 years (92% women). The patients were divided into daily, weekly, monthly, 3-monthly, and swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…Though these ranges are large, the authors did note that adherence and persistence were higher in formulations which required less frequent dosing and fracture rates were significantly lower in women with higher adherence (particularly a MPR > 80%) [45]. This finding is supported by data from national claims database which found that the MPR of bisphosphates rose with increasing interval between prescribed doses (from daily to 3 monthly), though some of the included medications were intravenously delivered [46].…”
Section: Consequences Of Poor Adherencementioning
confidence: 84%
“…Though these ranges are large, the authors did note that adherence and persistence were higher in formulations which required less frequent dosing and fracture rates were significantly lower in women with higher adherence (particularly a MPR > 80%) [45]. This finding is supported by data from national claims database which found that the MPR of bisphosphates rose with increasing interval between prescribed doses (from daily to 3 monthly), though some of the included medications were intravenously delivered [46].…”
Section: Consequences Of Poor Adherencementioning
confidence: 84%
“…Авторы сделали выводы, что при приеме препаратов, требующих более редкого приема, частота переломов была значительно ниже, а приверженность терапии были существенно выше по сравнению с другими видами терапии [34]. Этот вывод подтверждается результатами анализа данных национальной медицинской базы, установившими, что ИПП БФ повышается по мере увеличения интервала между приемом препарата [35].…”
Section: низкая приверженность пациентов терапии пероральными бисфосф...unclassified